Una sugerencia relativa a la inflación argentina - Wilkes, Heriberto G. A. (1966)
Proposes to relate national currency to the price of gold as divisor of everything, in the same way as some entities have been applying up to now when they have to measure wages and salaries by means of indexes or inflation factors. He refers to the "point" system used for the periodical adjustment of salaries of the Argentine teachers. Comments on the example given by a commercial enterprise of a nexus to a strong coin and the experience of a public service extensible to others than its own system. He also points out the error arising from measuring the price variation of a possession with reference to the index of wholesale prices from which new relative prices (or "points") result with no calculated unity. He is strongly against the generalization of the "point" system or indexes of different dimensions as in the case of the bringing up to date the value of pension assignments.